Strategi Pemasaran Produk Penghimpunan Dana Bank Syariah dalam Upaya Meningkatkan Pangsa Pasar Perbankan Syariah - Harmoko, Irfan (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2018)
Market share of sharia banking in Indonesa is low. It‟s acontradictif with the realy that Indonesia is a largest moslim population. One of the way to increase sharia bank market share is growth up the funding or DPK. Market segmentation is one of strategy that can be applied. In addition, giving high return, good banking facilities (ATM, CMS, mobile banking, internet banking) can also add attraction for customer to deposit funds the sharia bank.